Tertiary Education and Economic Growth of Nepal: An ARDL-ECM Analysis - Dangal, Dil Nath (Humanities and Social Sciences Journal, 2022)
This study examined the relationship between tertiary schooling and economic growth in Nepal. The autoregressive distributed-lagged (ARDL) bound test for cointegration and error-correction method (ECM) were employed. Time series data of 1989/90 to 2018/19 were taken into consideration. Updated time series and ARDL bounds test were applied for cointegration with ECM analysis to estimate the aimed relationship between variable of interests. Economic growth (RGDP) as dependent variable, education (GERT) as a regressor, and controlled variables––physical capital, labor force, and CPI––were used. The results of the study revealed cointegration between education and economic growth, confirming their long-run relationship. The negative and significant ECT1-t strengthened the presence of long-run relationship among RGDP and GERT. This study found tertiary schooling as a productivity enhancer of human capital in Nepal. Based on this finding, this study recommends promoting the tertiary schooling through adequate financing.